2011
DOI: 10.1007/s10549-011-1856-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative biomarker study of 514 matched cases of male and female breast cancer reveals gender-specific biological differences

Abstract: Male breast cancer remains understudied despite evidence of rising incidence. Using a co-ordinated multi-centre approach, we present the first large scale biomarker study to define and compare hormone receptor profiles and survival between male and female invasive breast cancer. We defined and compared hormone receptor profiles and survival between 251 male and 263 female breast cancers matched for grade, age, and lymph node status. Tissue microarrays were immunostained for ERα, ERβ1, -2, -5, PR, PRA, PRB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 60 publications
11
96
3
2
Order By: Relevance
“…In ERα-positive breast cancer cells, AR has been shown to limit ERα-mediated growth (Cops et al 2008, Peters et al 2009) indicating the propensity to confer better response in patients who are positive for both receptors. This finding is supported in MBC by clinical work in which ERα-positive/AR-positive patients had significantly better outcome compared to ERα-positive/AR-negative patients, and their hormone receptor immunohistochemical profiles illustrated co-clustering based on ER (both ERα and ERβ) and AR expression (Shaaban et al 2012). In FBC on the other hand, ERα clustered with progesterone receptor, whereas AR clustered with ERβ, suggesting an intrinsic difference in hormone receptor biology and hormone receptor dependencies between genders.…”
Section: Molecular Featuresmentioning
confidence: 64%
See 3 more Smart Citations
“…In ERα-positive breast cancer cells, AR has been shown to limit ERα-mediated growth (Cops et al 2008, Peters et al 2009) indicating the propensity to confer better response in patients who are positive for both receptors. This finding is supported in MBC by clinical work in which ERα-positive/AR-positive patients had significantly better outcome compared to ERα-positive/AR-negative patients, and their hormone receptor immunohistochemical profiles illustrated co-clustering based on ER (both ERα and ERβ) and AR expression (Shaaban et al 2012). In FBC on the other hand, ERα clustered with progesterone receptor, whereas AR clustered with ERβ, suggesting an intrinsic difference in hormone receptor biology and hormone receptor dependencies between genders.…”
Section: Molecular Featuresmentioning
confidence: 64%
“…Notably, AR is highly expressed in male breast cancers (Zhou et al 2014) and has been found to be indicative of good outcome in male breast (Shaaban et al 2012) and poor outcome in hormone-refractory prostate cancer (Buhmeida et al 2006). These discordant results may be indicative of inherent differences between breast and prostate cancer or they may highlight the importance of treatment setting in these studies as ERα/AR dual positivity has recently been shown to be associated with improved outcome (Li et al 2016).…”
Section: Molecular Featuresmentioning
confidence: 95%
See 2 more Smart Citations
“…Although there are similarities between MBC and FBC, there is also mounting evidence that they are quite different biologically. There is little proof that the prognostic features found in FBC are also valid for MBC (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%